Folklore texts of urban romance - Hayriyan, Lusine (Bulletin of Yerevan University B: Philology, 2024)
Armenian traditional music is accepted to be divided into three main branches: rural, urban folklore, and gusan-troubadour art. Urban musical folklore, in contrast to rural one, is mainly composed of literary or vernacular language. This field of folk music with its unique manifestations remains in the research focus of musicologists, ethnographers-philologists. The first systematic studies were carried out in the 20th century, producing opposite, contradictory conclusions. Some linguists and ethnographers still reject the idea of urban folklore, considering it a "distortion" of rural folklore tradition. According to another view, urban folklore is a unique historical and cultural phenomenon with a unique process of development and patterns. Each example of a city song goes through a special way of creation and dissemination (folklore text-folk melody, author’s text-folk melody, author’s word-music, same song difference with rural-urban parallels, popularization of a song by a famous author, folk versions of words or with a change of theme, urban song with rural folklore texts, words with different melody content, themes, etc.). Urban romances have certain patterns that are noticeable everywhere. One of the unique representations of urban romance is famous fadu. Fadu is descended from medieval Pyrenean (Spanish-Portuguese) romances and Portuguese folk quartets. Portuguese and Armenian urban musical folklore is comparable with certain motive commonalities. The symbols of the Armenian-Portuguese romances are also comparable. With certain transformations everyday romances continue to remain in the realm of modern urban music culture.